A creative problem-solving-oriented electronic student worksheet assisted by environmental sensors to enhance higher-order thinking skills and environmental awareness - Pertiwi, Sindi Putri; Jalmo , Tri; Diawati, Chansyanah (Universitas Islam Negeri Raden Intan Lampung, 2026)
Higher-order thinking skills and environmental awareness are essential competencies for addressing climate change through science education. This study aimed to develop an electronic student worksheet for creative problem-solving (CPS) assisted by environmental sensors and to evaluate its validity, practicality, and effectiveness. The study employed a Research and Development method using the ADDIE model, followed by a quasi-experimental pretest–posttest control group design involving 25 students in the experimental class and 20 in the control class. Data were collected using validation sheets, practicality questionnaires, Higher Order Thinking Skills (HOTS) tests, environmental awareness questionnaires, and learning implementation observations. The developed electronic student worksheet achieved a validity score of 94.31% (very valid). Practicality evaluation showed teacher responses at 93%, student responses at 93%, and learning implementation at 85%. The higher-order thinking skills N-Gain score reached 0.6616 (66.16%) with a large effect size (Cohen's d = 4.25), while environmental awareness achieved an N-Gain score of 0.5911 (59.11%) with a large effect size (Cohen's d = 3.98). These findings demonstrate that integrating real-time environmental sensor data into an electronic student worksheet effectively improves students' HOTS and environmental awareness.